2014
DOI: 10.15312/eurasianjvetsci.201415912
|View full text |Cite
|
Sign up to set email alerts
|

Some morphological traits of Tarsus Çatalburun breed of Turkish hunting dog

Abstract: Amaç: Çalışma yetiştirici elinde bulunan Tarsus Çatalburun ırkı Türk av köpeklerinin bazı morfolojik özelliklerini belirlemek amacıyla, anayurtları olan Tarsus ve Adana kentlerinde yapıldı. Gereç ve Yöntem: Araştırmada, yaşları 2-6 arasında değişen 10'u dişi 12'si erkek olmak üzere toplam 22 Çatalburun köpeği kullanıldı. Cinsiyet gruplarının tüm değişkenler için karşılaştırmalarında Student-t testinden yararlanıldı. Bulgular: Tarsus Çatalburun köpekleri ile ilgili ilklerden olan bu çalışmada, 13 farklı ölçüm y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Brachycephalic breed dogs are also at increased risk for cleft lip and/or palate (CL/P), but not so much as the Spanish Pachón Navarro and the Turkish Catalburun. For both, CL/P is a breed-defining feature: folklore maintains that their “split-nose” lends these dogs superior scenting abilities needed for hunting [ 36 , 37 ]. Given these breeds’ scarcity and small following, it is unclear to what extent CL/P affects these animals’ quality of life.…”
Section: Reviewmentioning
confidence: 99%
“…Brachycephalic breed dogs are also at increased risk for cleft lip and/or palate (CL/P), but not so much as the Spanish Pachón Navarro and the Turkish Catalburun. For both, CL/P is a breed-defining feature: folklore maintains that their “split-nose” lends these dogs superior scenting abilities needed for hunting [ 36 , 37 ]. Given these breeds’ scarcity and small following, it is unclear to what extent CL/P affects these animals’ quality of life.…”
Section: Reviewmentioning
confidence: 99%
“…The skull is an important anatomical structure to discern dog breeds and wolves from dogs, plus add refs on wolves. In the skull literature studies, the Carnivors [1,9,11,12,28], Kangal and Malakli dogs [10,17,21], Tarsus Çatalburun dog [18], German wolf dog [19,20], Gray wolf [14]. It has been found that there are many studies on skull morphology and morphometry in Lynx [7], Red fox [22], Vulpes [25] and Golgen jackal [15].…”
Section: Introductionmentioning
confidence: 99%